Matrigel Scaffolding Enhances BMP9-induced Bone Formation in Dental Follicle Stem/Precursor Cells - Fu, Tiwei (Int J Med Sci, 2019)
Bone tissue engineering requires a combination of cells, efficient biochemical and physicochemical factors, and biocompatible scaffolds. In this study, we evaluated the potential use of injectable Matrigel as a scaffold for the delivery of rat dental follicle stem/precursor cells (rDFSCs) transduced by bone morphogenetic protein (BMP) 9 to enhance osteogenic differentiation in vitro and promote ectopic bone formation in vivo. Recombinant adenovirus was used to overexpress BMP9 in rDFSCs. Alkaline phosphatase activity was measured using a histochemical staining assay and a chemiluminescence assay kit. Quantitative real-time polymerase chain reaction was used to determine mRNA expression levels of bone-related genes including distal-less homeobox 5 (DLX5), osteopontin (OPN), osterix (Osx), and runt-related transcription factor 2 (Runx2). Matrix mineralization was examined by Alizarin Red S staining. rDFSCs proliferation was analyzed using the Cell Counting Kit-8 assay. Subcutaneous implantation of rDFSCs-containing Matrigel scaffolds was used, and micro-computed tomography analysis, histological evaluation, and trichrome staining of implants extracted at 6 weeks were performed. We found that BMP9 enhanced alkaline phosphatase activity and mineralization in rDFSCs. The expression of bone-related genes (DLX5, OPN, Osx, and Runx2) was also increased as a result of BMP9 stimulation. Micro-computed tomography analysis and histological evaluation revealed that the bone masses retrieved from BMP9-overexpressing rDFSCs were significantly more pronounced in those with than in those without Matrigel. Our results suggest that BMP9 effectively promote osteogenic differentiation of rDFSCs, and Matrigel facilitate BMP9-induced osteogenesis of rDFSCs in vivo.